Humeral intramedullary nail bending following trauma: a case report - Siem A. Willems; Alexander P. A. Greeven (Journal of Trauma and Injury)
The surgical approach for humeral implant failure can be challenging due to neurovascular anatomy and the possible necessity of osteosynthesis removal. We present a rare case of humeral nail bending after secondary trauma in a patient with preexistent nonunion of the humerus after intramedullary nailing. During revision surgery, the nail was sawed in half and the distal part was removed, followed by plate osteosynthesis with cable fixation to achieve absolute stability. The patient regained a full range of motion 1 year after surgery, and complete healing of the fracture was seen on imaging.